INTERIOR DESIGN STUDENTS' DIGITAL TECHNOLOGY EXPERIENCES IN CREATIVE DESIGN PROCESS - Anıl SÜVARİ; Merve Buldaç (International Journal of Eurasia Social Sciences, 2018)
The theme of this work is assessing the use of digital technology in relation to the creative thinking process in Interior Design education. For this purpose, the effects of digital technologies on the creative design development process in interior design education were examined through student experiences. 4 yeared students (39 people) in Interior Design department of a state university located in the Central Anatolia Region in Turkey are the participants of the study. Identification of participants; volunteer to research, basic design / art education, computer-aided design courses and graduation completion project. Four elements (fluency, flexibility, originality and enrichment) defined by Torrance's creativity, who is important contributions to literacy in the measurement of creativity, were asked and open-ended questions were asked to the students. In the research, phenomenological approach was used from qualitative research methods and data were evaluated by content data analysis. Among the findings, it has been understood that students use digital technologies for research purposes on internet, technical drawings in computer environment, making 3D visualizations and preparing documents with text-image support. With the findings, the results of the students' experiences about digital technology and creative process, how they interpreted and interpreted this relation. Positively significant results are that digital technologies enhance design alternatives, improve the quality of interior design and ease the design intervention. The inability to benefit from the positive effects of hand drawing on creativity and the use of ready-made materials to destroy the original design are the negative consequences of the use of digital technology.